On Enabling Attribute-Based Encryption to Be Traceable Against Traitors. (23rd July 2020) - Liu, Zhen; Huang, Qiong; Wong, Duncan S
Abstract: Attribute-based encryption (ABE) is a versatile one-to-many encryption primitive, which enables fine-grained access control over encrypted data. Due to its promising applications in practice, ABE schemes with high efficiency, security and expressivity have been continuously emerging. On the other hand, due to the nature of ABE, a malicious user may abuse its decryption privilege. Therefore, being able to identify such a malicious user is crucial towards the practicality of ABE. Although some specific ABE schemes in the literature enjoys the tracing function, they are only proceeded case by case. Most of the ABE schemes do not support traceability. It is thus meaningful and important to have a generic way of equipping any ABE scheme with traceability . In this work, we partially solve the aforementioned problem. Namely, we propose a way of transforming (non-traceable) ABE schemes satisfying certain requirements to fully collusion-resistant black-box traceable ABE schemes, which adds only $O(\sqrt{\mathcal{K}})$ elements to the ciphertext where ${\mathcal{K}}$ is the number of users in the system. And to demonstrate the practicability of our transformation, we show how to convert a couple of existing non-traceable ABE schemes to support traceability.